QR Code-Based Picture Story Book Media to Improve Analytical Thinking on Elemental Materials in Class 5 Literary Work at State 4 Purwodadi Primary School Malang District - Dwi Yoni Hidayati; Cindya Alfi; Mohamad Fatih (Edumaspul: Jurnal Pendidikan, 2024)
A country needs to invest in its education. Without education, the people of the country will not understand what independence means. The public education system in this country will be run independently. Apart from that, the people will also have superior qualities that will be beneficial for the country. However, based on empirical data in this sector, there are limitations in the use and accessibility of learning media. Teachers will actually benefit from developing learning media because they will be better able to explain subject matter to students. Therefore, this research was conducted at SD Negeri 4 Purwodadi, Malang Regency. One type of research and development (R&D) is this research. The Borg and Gall research model was used in this research. The research findings are based on material expert scores which are considered "very valid" with a percentage of 87.5%. The material expert's assessment was assessed as "very valid" with a percentage of 95%. The linguist's assessment was considered "very valid" with a proportion of 90%. Validation of media suitability is rated "very valid" with a score of 90. Validation of test questions has a rating of 83% which means "quite valid". The proportion of media eligibility is 97%. Included in the "Very Appropriate, no need to revise" category when interpreted according to the validity criteria table. With a percentage of 73%, the feasibility of expert validation of linguists falls in the range of 70.01 – 85.00%. Enter under the title "Good, Appropriate, no need for revision" in the validity criteria table. The Ngain categorization that meets the "high" criteria is placed in the 0.70 < n < 1.00 group. Thus, it can be said that grade 5 students at SD Negeri 04 Purwodadi can develop their analytical thinking skills by using picture story books that depict elements contained in literary works.